#TITLE_ALTERNATIVE# - MUHAMMAD RIDWAN [NIM : 25002043]; Pembimbing: Prof. Ir. Ofyar Z. Tamin, M.Sc.(Eng), MIHT, Ph.D, TEUKU
The development of transportation infrastructure, particularly in big cities in Indonesia, is needed as a result of the economic growth and population dynamism. However, the funding for the development has becomes one of the constraints for the Indonesian government. The private investment sector, therefore, becomes one of the solutions for such a constraint, particularly for funding the road network development or in particular toll development. As far as the investment in toll road is concerned, the private investors are more interested in looking at the financial feasibility aspect than the other investment aspects, for example: economy aspect. In terms of financial feasibility, one of the parameters referred to by the private investor is the guarantee of the reliability of the investment return during the concession period. One of the indicators in the guarantee of the reliability of the investment return is the tariff toll rate. In fact, the tariff toll rate has been one of the problems in the toll investment in Indonesia. In addition, the government has not made guidance on the percentage of the profit of the vehicle operational cost (PVOC) or a model of optimum toll tariff that can be used by the private investors to maximize their revenue. The model of optimum toll tariff concerns a mathematical model which is based on the price elasticity demand theory in which the demand decreases when the price is increased.The purpose of this study is to identify the disparity range of the investment return on the basis of the system of optimum toll tariff and government toll tariff in relation to JOORR construction. In specific, the study is analyzing the toll construction along the Jabodetabek zone under the infrastructure construction plan of JOORR for as long as 30 years starting from the year of 2020 to 2050. The model used to calculate the vehicle operational cost for the system of government toll tariff is the one developed by PCI, while for the system of optimum toll tariff, the model to calculate the vehicle operational cost is the one developed by LAPI ITB. As for predicting the travel demand, both the SATURN software is used in the two models. In regard with the model for determining the government toll tariff, SATASS (inelastic assignment) module is used whereas the model for determining the optimum toll tariff SATEASY (elastic assignment) module is used. The analysis result shows that with 7% of tariff rise for every two years and with discount rate of 10%, the disparity range of the government tariff toll base is 17% higher than the optimum tariff toll. Under the simulation of inelastic method, the number of JOORR toll users is predicted to be relatively the same or having a small disparity. And under the simulation of elastic method, before the toll tariff rises, the disparity range is 0.024% and the disparity range is 1.38% after the toll tariff rises. With respect to the return of investment period that is analyzed by payback period method, a relatively the same return of investment period is obtained, namely: 21 years and 3 months for the system of government toll tariff and 22 years and five months for the system of optimum toll tariff. Under the discounted payback method, the same analysis result is also obtained where the return of investment period is relatively the same, namely: 21 years and 4 months for the system of government toll tariff and 22 years and 6 months for the system optimum toll tariff, or 1 year and 2 months deviation.